DIDACTIC CONDITIONS UNDERSTANDING SCIENTIFIC MATHEMATICAL TEXT STUDENTS – FUTURE PRIMARY SCHOOL TEACHERS - Sergeeva, Larisa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article substantiates the necessity of understanding mathematical text in the process of training of students – future primary school teachers. The features of the understanding of the subject area of "mathematics" on the basis of the analysis of the specificity of mathematical texts. The article presents the didactic conditions of understanding mathematical texts with students in order to improve the quality of mathematical and pedagogical education of future primary school teachers. Describes the tools and methods to ensure understanding of mathematical content by the students. The conducted research allowed to establish the effect of implementing the selected conditions on the overcoming of formalism in the assimilation of mathematics by students.